Therapeutic potential of eccentric exercises for age-related muscle atrophy - Jae-Young Lim (Integrative Medicine Research)
Recent studies have focused on evidence-based interventions to prevent mobility decline and enhance physical performance in older adults. Several modalities, in addition to traditional strengthening programs, have been designed to manage age-related functional decline more effectively. In this study, we reviewed the current relevant literatures to assess the therapeutic potential of eccentric exercises for age-related muscle atrophy (sarcopenia). Age-related changes in human skeletal muscle, and their relationship with physical performance, are discussed with reference to in vitro physiologic and human biomechanics studies. An overview of issues relevant to sarcopenia is provided in the context of the recent consensus on the diagnosis and management of the condition. A decline in mobility among the aging population is closely linked with changes in the muscle force–velocity relationship. Interventions based specifically on increasing velocity and eccentric strength can improve function more effectively compared with traditional strengthening programs. Eccentric strengthening programs are introduced as a specific method for improving both muscle force and velocity. To be more effective, exercise interventions for older adults should focus on enhancing the muscle force–velocity relationship. Exercises that can be performed easily, and that utilize eccentric strength (which is relatively spared during the aging process), are needed to improve both muscle force and velocity.